Gerstmann-Sträussler-Scheinker disease revisited: accumulation of covalently-linked multimers of internal prion protein fragments - Cracco, Laura (Acta Neuropathol Commun, 2019)
Despite their phenotypic heterogeneity, most human prion diseases belong to two broadly defined groups: Creutzfeldt-Jakob disease (CJD) and Gerstmann-Sträussler-Scheinker disease (GSS). While the structural characteristics of the disease-related proteinase K-resistant prion protein (resPrP(D)) associated with the CJD group are fairly well established, many features of GSS-associated resPrP(D) are unclear. Electrophoretic profiles of resPrP(D) associated with GSS variants typically show 6–8 kDa bands corresponding to the internal PrP fragments as well as a variable number of higher molecular weight bands, the molecular nature of which has not been investigated. Here we have performed systematic studies of purified resPrP(D) species extracted from GSS cases with the A117V (GSS(A117V)) and F198S (GSS(F198S)) PrP gene mutations. The combined analysis based on epitope mapping, deglycosylation treatment and direct amino acid sequencing by mass spectrometry provided a conclusive evidence that high molecular weight resPrP(D) species seen in electrophoretic profiles represent covalently-linked multimers of the internal ~ 7 and ~ 8 kDa fragments. This finding reveals a mechanism of resPrP(D) aggregate formation that has not been previously established in prion diseases. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40478-019-0734-2) contains supplementary material, which is available to authorized users.